Unsur Jawa dalam Iluminasi Al-Qur’an - Syahrazad, Hanan (SUHUF, 2021)
The paper aims at knowing the visual forms and decorations found in the Qur’an manuscripts being copied at Pura Pakualaman, Yogyakarta, which are described by using the visual unit model of craft art. The manuscripts of the Pura Pakualaman collection are stored in the Pura Pakualaman library, including the five Qur'an manuscripts. Two of them have a variety of decorations, namely one mushaf with a decorative wedana renggan, and the other mushaf with an ornamental wedana gapura renggan with a variety of flora decorations. Unlike the Pura Pakualaman manuscripts in general, which have a philosophical connection between the text and its decoration, the ornaments found in this manuscript do not have a meaningful relationship between the text of the Qur’an verse and the decorations that surrounded it. The ornamental variety of wedana renggan and wedana gapura renggan that appear in the Qur'an manuscripts shows the influence of the Javanese script writing tradition in the copying the Qur'an manuscripts in Java, especially at the Pura Pakualaman.